2021
DOI: 10.1249/mss.0000000000002841
|View full text |Cite
|
Sign up to set email alerts
|

Regular Aerobic Exercise Attenuates Pain and Anxiety in Mice by Restoring Serotonin-Modulated Synaptic Plasticity in the Anterior Cingulate Cortex

Abstract: PurposeClinical studies found that regular aerobic exercise has analgesic and antianxiety effects; however, the underlying neural mechanisms remain unclear. Multiple studies have suggested that regular aerobic exercise may exert brain-protective effects by promoting the release of serotonin, which may be a pain modulator. Anterior cingulate cortex (ACC) is a key brain area for pain information processing, receiving dense serotonergic innervation. As a result, we hypothesized that exercise may increase the rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
2
18
0
1
Order By: Relevance
“…We first compared 5-HT levels between animals in the control group and the PCPA group to examine the depletion effect on blood 5-HT under PCPA [300 mg/kg, intraperitoneal injection (i.p.)]. The comparison depicted significant differences ( Figure 1A ), consistent with the previous studies ( Farabollini et al, 1988 ; Zhou et al, 2022b ).…”
Section: Resultssupporting
confidence: 82%
“…We first compared 5-HT levels between animals in the control group and the PCPA group to examine the depletion effect on blood 5-HT under PCPA [300 mg/kg, intraperitoneal injection (i.p.)]. The comparison depicted significant differences ( Figure 1A ), consistent with the previous studies ( Farabollini et al, 1988 ; Zhou et al, 2022b ).…”
Section: Resultssupporting
confidence: 82%
“…In addition, extensive studies from humans and rodents have shown the fundamental roles of the ACC in acute and chronic pain [ 71 ]. For instance, serotonin in the ACC contributes to relieving pain and anxiety through synaptic plasticity triggered by regular aerobic exercise [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new study described that regular aerobic exercise had significant effects in relieving pain and concomitant anxiety in the chronic inflammatory pain model. Regular aerobic exercise could increase 5-HT release and attenuate pain-induced LTP occlusion in the ACC through the 5-HT 1A and 5-HT 7 receptors ( Zhou et al, 2022 ). Therefore, 5-HT may be modulating injury-related anxiety by directly or indirectly changing the pre-LTP of excitatory transmission in the ACC.…”
Section: Contributions Of the 5-ht System To Injury-related Anxietymentioning
confidence: 99%